2013
DOI: 10.1007/s00213-013-3231-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of estrogen and testosterone on auditory sensory gating in rats

Abstract: Chronic estrogen replacement in OVX rats protected against sensory gating deficits caused by direct dopamine D1/D2 receptor stimulation. These data could indicate a possible mechanism by which estrogen exerts a protective action in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
1
2
0
1
Order By: Relevance
“…The present data confirm previous findings where treatment with 17β-oestradiol prevented dopamine-mediated deficits in PPI , as well as dopamine-mediated disruptions of other paradigms, including N1 sensory gating (Thwaites et al, 2014) and latent inhibition (Arad and Weiner, 2010). We have suggested that oestradiol can exert this effect by down-regulating dopamine D 2 receptors in the nucleus accumbens, however changes in the density of the dopamine transporter may also play a role .…”
Section: Discussionsupporting
confidence: 92%
“…The present data confirm previous findings where treatment with 17β-oestradiol prevented dopamine-mediated deficits in PPI , as well as dopamine-mediated disruptions of other paradigms, including N1 sensory gating (Thwaites et al, 2014) and latent inhibition (Arad and Weiner, 2010). We have suggested that oestradiol can exert this effect by down-regulating dopamine D 2 receptors in the nucleus accumbens, however changes in the density of the dopamine transporter may also play a role .…”
Section: Discussionsupporting
confidence: 92%
“…This is important because various environmental conditions, such as housing, are known to affect behaviour . Thus, in the present study, we used our established chronic 17β‐oestradiol treatment model in rats and measured three widely used, validated behaviours relevant to depression: SPT, FST and NORT. We also measured activity in the open field test and the novelty suppressed feeding test aiming to evaluate whether locomotion, anxiety and motivation are implicated in the effects of chronic 17β‐oestradiol treatment on depressive‐like behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Among the ovarian steroid influences on PPI, estradiol has gained most interest, due to higher PPI in the follicular, relative to the luteal, phase (Kumari, 2011). In addition, estrogen induces a dose-dependent increase in PPI in ovariectomized rats (Charitidi et al, 2012;Van den Buuse and Eikelis, 2001), and prevents 5-HT 1A -, dopamine-, and NMDA receptorinduced disruptions of PPI (Gogos et al, 2010(Gogos et al, , 2012(Gogos et al, , 2006Gogos and Van den Buuse, 2004;Thwaites et al, 2014). While a role for progesterone in PPI has been suggested (Kumari et al, 2010), this effect is presumably not mediated by GABA-active progesterone metabolites (Kask et al, 2009).…”
Section: Lower Ppi In Pregnant Women Compared To Healthy Non-pregnantmentioning
confidence: 99%